Impact and frequency of misdiagnosis of appendicitis in pediatric patients with gastroenteritis in a developing country - Pastor Escárcega-Fujigaki; Guillermo Hernández-Peredo-Rezk; Gerardo Alonso-Acosta; Keren-Hapuc Vargas-Amador (Global Pediatrics)
Aim: Appendicitis manifests with atypical symptoms in a large percentage of patients, leading to diagnostic errors that delay diagnosis. This study aimed to evaluate the impact and frequency of appendicitis being incorrectly diagnosed as gastroenteritis in a developing country. Methods: This prospective, comparative study included 207 pediatric patients with appendicitis divided into two groups: group A, with 117 (56.5 %) patients with diagnostic errors, and group B, with 90 (43.4 %) patients without diagnostic errors. Clinical, laboratory, and imaging data were compared using the Mann–Whitney tests, odds ratio (OR), and 95 % confidence interval (CI) with statistical significance set at p-value <0.05. Results: The diagnosis was confused with gastroenteritis in 66 (56.4 %) patients, causing a delay in surgical management, which was statistically significant (OR: 2.25; 95 % CI: 1.23–4.09; p < 0.005) when compared with group B. The second most common cause of confusion was colitis, which was observed in 40 (34.2 %) patients. Group A had a large number of perforated appendicitis cases (OR: 3.22; 95 % CI: 1.81–5.72; p < 0.01), with more days till oral administration initiation (OR: 3.68; 95 % CI: 1.32–10.27; p < 0.01) and longer hospital stays (OR: 6.83; 95 % CI: 1.85–25.11; p < 0.01). Furthermore, general practitioners more frequently had diagnostic errors than pediatricians (OR: 0.17; 95 % CI: 0.07–0.43; p < 0.01). Conclusions: The diagnosis of appendicitis was confused with gastroenteritis or colitis in majority of pediatric patients. Practitioners should be aware of the possibility of appendicitis in patients presenting with abdominal pain, diarrhea, or fever. Level of Evidence: III